Explanation
the distance between 2 points P1 and P2 is given by:
[tex]\begin{gathered} \text{distance}=\sqrt[]{(x_2-x_1)^2+(y_2-y_1)^2} \\ \text{where} \\ P1(x_1,y_1) \\ P2(x_2,y_2) \end{gathered}[/tex]Step 1
Let
P1=(4,3)
P2=(9,15)
replace
[tex]\begin{gathered} \text{distance}=\sqrt[]{(x_2-x_1)^2+(y_2-y_1)^2} \\ \text{distance}=\sqrt[]{(9-4)^2+(15-3)^2} \\ \text{distance}=\sqrt[]{(5)^2+(12)^2} \\ \text{distance}=\sqrt[]{25+144^{}} \\ \text{distance}=\sqrt[]{169} \\ \text{also} \\ \text{distance}=13 \end{gathered}[/tex]I hope this help you